Pola adaptasi mahasiswa baru terhadap kegiatan akademik kampus - Wotan, Handhala Al Ashshidie (Maliki Interdisciplinary Journal, 2024)
Entering the world of lectures, of course, new students will definitely feel confusion, anxiety, fear and other mixed feelings. A process is needed to block or reduce these feelings of anxiety and fear. This article discusses the beginning of student life on campus and how students adjust to their new life at college. This article aims to examine how students face the challenges that exist in the world of college and what challenges new students face.